2015
DOI: 10.1037/neu0000180
|View full text |Cite
|
Sign up to set email alerts
|

Habitual prospective memory in HIV disease.

Abstract: HIV-associated neurocognitive disorders (HAND) are associated with deficits in prospective memory (PM). However, most PM research in HIV has used single-event tasks as opposed to habitual PM paradigms, which may be more relevant to clinical populations for whom many healthcare behaviors must be performed both frequently and routinely. The current study examined habitual PM and its associations with real-world functioning outcomes in 36 HIV+ individuals with HAND (HAND+), 70 HIV+ individuals without HAND (HAND-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
2
5
0
1
Order By: Relevance
“…Effect sizes were not reliably available across these analyses, which were exclusively secondary or tertiary subanalyses. With regard to HIV treatment factors, five studies have reported null associations between cART status and PM (e.g., e.g., Doyle et al, 2015a; Martin et al, 2007; Weber et al, 2011; Woods et al, 2010; Zogg et al, 2010), which was consistent with analyses from our own cohort (see Figure 2). Of course, such findings are quite limited in the cART era given that most participants in research are prescribed therapy.…”
Section: Disease Factors and Pm In Hivsupporting
confidence: 89%
“…Effect sizes were not reliably available across these analyses, which were exclusively secondary or tertiary subanalyses. With regard to HIV treatment factors, five studies have reported null associations between cART status and PM (e.g., e.g., Doyle et al, 2015a; Martin et al, 2007; Weber et al, 2011; Woods et al, 2010; Zogg et al, 2010), which was consistent with analyses from our own cohort (see Figure 2). Of course, such findings are quite limited in the cART era given that most participants in research are prescribed therapy.…”
Section: Disease Factors and Pm In Hivsupporting
confidence: 89%
“…Moreover, less than a quarter of the participants who received content-free cueing indicated that they would use this PM support in daily life. There is still reason for hope with content free cuing, since better naturalistic PM accuracy was associated with more frequent use of the STOP approach via the diary entries, which aligns with data showing that HIV is associated with diminished strategic monitoring for PM cues (e.g., Doyle et al, 2015). Similar approaches to enhancing monitoring have been effective in improving naturalistic PM in persons with traumatic brain injury who underwent extensive training (e.g., Fish et al, 2007; Gracey et al, 2017) and in improving mulititasking in the laboratory among middle-aged PLWH who received brief training (Casaletto et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…For example, Avci et al (2016) reported that 72% of older PLWH (vs. 51% of older HIV– individuals) failed a naturalistic PM task in which they were asked to telephone an examiner 24 hr after their study visit and report how many hours they slept. Across studies of PLWH and aging, naturalistic time-based PM failures are associated with lower PM capacity as measured in the laboratory, including lapses in cue detection (Kamat et al, 2014; Zogg et al, 2010) and habitual (which are intentions that occur frequently and routinely; Meacham & Leiman, 1982) PM (Doyle et al, 2015). Naturalistic time-based PM failures are stable over one year among older PLWH (Kordovski, Sullivan, Tierney, & Woods, 2020) and are associated with poorer medication management (Woods et al, 2008).…”
mentioning
confidence: 99%
“…Alternative neuropsychological assessments seeking a pattern of deficits that would be more sensitive and specific is ongoing, with interesting observations that prospective memory (ability to remember to remember) might be a particularly informative focus. [16] A serious challenge for use of the Frascati criteria is how to detect and classify functional impairment. Commonly self-report is the only evidence used, but recent evaluations suggest that this is an insecure determination.…”
Section: Biomarkers and Handmentioning
confidence: 99%